2004
DOI: 10.1074/jbc.m313115200
|View full text |Cite
|
Sign up to set email alerts
|

The MAM (Meprin/A5-protein/PTPmu) Domain Is a Homophilic Binding Site Promoting the Lateral Dimerization of Receptor-like Protein-tyrosine Phosphatase μ

Abstract: The MAM (meprin/A5-protein/PTPmu) domain is present in numerous proteins with diverse functions. PTP belongs to the MAM-containing subclass of protein-tyrosine phosphatases (PTP) able to promote cell-to-cell adhesion. Here we provide experimental evidence that the MAM domain is a homophilic binding site of PTP. We demonstrate that the MAM domain forms oligomers in solution and binds to the PTP ectodomain at the cell surface. The presence of two disulfide bridges in the MAM molecule was evidenced and their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 45 publications
4
60
0
1
Order By: Relevance
“…It is also plausible that MDGA1 is required for later path-finding and targeting processes, but not at the onset of its expression. and mediates lateral (cis) homophilic interactions in neuropilin-1 (Nakamura et al, 1998) and PTPµ (Cismasiu et al, 2004). Our experiments do not exclude the potential of homophilic association among MDGA1 molecules, that might not be detected by the overlay assay used here.…”
Section: Discussionmentioning
confidence: 68%
“…It is also plausible that MDGA1 is required for later path-finding and targeting processes, but not at the onset of its expression. and mediates lateral (cis) homophilic interactions in neuropilin-1 (Nakamura et al, 1998) and PTPµ (Cismasiu et al, 2004). Our experiments do not exclude the potential of homophilic association among MDGA1 molecules, that might not be detected by the overlay assay used here.…”
Section: Discussionmentioning
confidence: 68%
“…Although there is evidence that the intradomain disulfide bridges in MAM domains in proteins such as protein-tyrosine phosphatase are essential for MAM homophilic interactions, there is no evidence for interdomain disulfide bridging in MAM domains in proteins other than meprins (12). The finding herein that the ␤C274A mutant has full enzymatic activity and results in the formation of a noncovalent meprin dimer indicates that the meprin ␤ subunit has a dimerization interface that is not dependent on intersubunit disulfide bridges.…”
Section: Table Imentioning
confidence: 62%
“…1). The MAM domain is present in many cell surface proteins and is thought to be involved in cell-cell adhesion, protein-protein interactions, and signal transduction (12). The TRAF domain is found in a diverse population of intracellular proteins and is also involved in protein associations and signal transduction; meprins are the only plasma membrane and extracellular proteins known to contain TRAF domains (13).…”
mentioning
confidence: 99%
“…Several MAM domain-containing proteins later identified, including zonadhesin [19], nephronectin [20], POEM [21], and neuropilins [22], have been shown to be involved in different aspects of cell adhesion and migration. It has been reported that the MAM domain mediates lateral (cis) homophilic interactions in PTP μ and κ [15,23] and neuropilin-1 [24,25]. In the developing chicken nervous system MDGA1 heterophilically interacts with axon-rich regions mainly through its MAM domain, and with differentiating muscle through its Ig-repeat-containing Nterminal region [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the GPIlinked IgSF proteins are involved in a variety of specific cell-cell interactions and/or in migration, such as LAMP, BIG-1, neurotrimin, CEPU-1, GP55 [7][8][9], CEA, CEACAM-6, NCAM p120 [10][11][12], F3/F11/contactin and TAG1/axonin-1 [13,14]. In addition, the presence of the MAM and/or Ig domains confers to these proteins the capacity to interact with other cells through homophilic and/or heterophilic interactions [2,4,15].…”
Section: Introductionmentioning
confidence: 99%